2009
DOI: 10.1525/srsp.2009.6.4.25
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality and intimacy in assisted living: Residents’ perspectives and experiences

Abstract: The assisted living industry provides residential, medical, nutritional, functional, and social services for approximately 1 million older adults in the United States. Despite their holistic approach to person-centered care and their emphasis on a consumer-empowered, social environment, assisted living providers pay scant attention to clients’ sexual needs. In this article, the authors discuss the realities of sex and intimacy in assisted living from the perspectives of residents, families, managers, and staff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 43 publications
(41 reference statements)
3
90
0
1
Order By: Relevance
“…Regarding data collection, one study utilised focus groups (Stein et al, 2010) and one study used a combination of observation and conversational interviews (Frankowski & Clark, 2009); the remaining studies collected data via semi-structured interviews. The method of analysis varied, although three studies did not specify their data analysis procedures (Frankowski & Clark, 2009;Nay, 1992;Röndahl, Innala, & Carlsson, 2006). Whilst all studies reported aims relating to individuals' experiences of sexuality, research questions varied.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding data collection, one study utilised focus groups (Stein et al, 2010) and one study used a combination of observation and conversational interviews (Frankowski & Clark, 2009); the remaining studies collected data via semi-structured interviews. The method of analysis varied, although three studies did not specify their data analysis procedures (Frankowski & Clark, 2009;Nay, 1992;Röndahl, Innala, & Carlsson, 2006). Whilst all studies reported aims relating to individuals' experiences of sexuality, research questions varied.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies (Frankowski & Clark, 2009;Nay, 1992) identified research questions post-data collection; understanding sexuality experiences was not the primary question asked of the data in these studies. Jootun, McGhee, and Marland (2009) argue that the inclusion of a reflexive account should be part of qualitative enquiry to increase the rigour of the research process and add credibility.…”
Section: Tablementioning
confidence: 99%
See 3 more Smart Citations